Hitler 1936 - 1945 : nemesis - Kershaw, Ian 1943- (Norton & Company, 2000)
Drawing on many previously underutilized resources--including the diaries of Joseph Goebbels--a portrait of Hitler encompasses events preceding World War II as well as the war years